THE INFLUENCE OF NUMBER HEAD TOGETHER STRATEGY AND STUDENTS’ LEARNING STYLES TOWARD READING COMPREHENSION ACHIEVEMENT THE TENTH GRADE STUDENTS AT ISLAMIC SENIOR HIGH SCHOOL PATRA MANDIRI OF PALEMBANG - Rahmat Wijaya (Universitas PGRI Palembang, 2019)
AbstractReading is a fundamental skill for learning and getting success in school and in life since more knowledge, joy, success, and career development can be gained through this activity. Determining the most suitable strategies and methods for reading activities may facilitate the students’ reading achievements. To solve the problem the researcher offered NHT Strategy to improve their reading ability. This research was investigated the influence of NHT Strategy and Students Learning Styles toward reading comprehension achievement to the Tenth grade students at Islamic Senior High School Patra Mandiri of Palembang. The population of the study was the tenth grade students at Islamic Senior High School Patra Mandiri of Palembang in the academic year 2017-2018 consisting of 320 students. From population, 70 students were taken as the research sample. 35 students represented in an experimental class and the rest of them were in the control class. In carrying out this research, the researcher selected two groups randomly used factorial design. In analyzing the data, researcher used statistics analysis and two-way ANOVA in SPSS16. The data distributions were considered normal, it was proved by statistic calculation of normality test which shows that p-output was higher than α 0,05. Based on the result of calculating using independent t-test, it was found as follows: First, based on the result of statistic calculation, it was found that the p-output was lower than α 0,05 it means that H1 accepted. Second, based on the result was found that the p-output was higher than α 0,05, it means that Ho accepted and H2 rejected. Third, based on the result it was found that the p-output was higher than α 0,05, it means that H3 rejected and Ho accepted. Fourth, based on the result it was found that the p-output was lower than α 0,05, it means that H4 accepted. And at last, the calculation analysis measuring an interaction effect between students’ reading comprehension achievement using NHT Strategy and conventional strategy towards students’ learning styles (visual and auditory learning style) found the p-output was lower than mean significant difference at the 0,05 level. It means that an interaction effect was found. It is concluded that Ho is rejected and Ha is accepted.Keywords: NHT Strategy, Students Learning Style, Reading Comprehension Achievement